Leading Teams #2: Stages of Group Development - Annie Ferguson Muscato; Sarah A. Bush; Laura L. Greenhaw; Carrie N. Baker (EDIS)
Most organizations rely on strong, effective groups and teams to operate. Many theories and models related to teams and team development exist. However, Tuckman and Jensen’s (1977) model of group development is still the most used (Fritz et al., 2005). In this article, we outline the five stages of small-group development (Tuckman & Jensen, 1977). Team members and leaders can use this model to improve their effectiveness (Burns, 1995). In the Leading Teams series, we discuss each stage in depth and provide actions leaders can use to guide their teams through each stage.